Association of personal network attributes with clean cooking adoption in rural South India. (16th June 2021) - Kumar, Praveen; McCafferty, Liam; Dhand, Amar; Rao, Smitha; Díaz-Valdés, Antonia; Tabak, Rachel G; Brownson, Ross C; Yadama, Gautam N
Abstract: Adoption of liquefied petroleum gas (LPG) is the primary policy approach in India to transition rural poor communities toward clean cooking behavior. Prior clean cooking studies show that affordability, accessibility, and awareness impact LPG adoption in India. There is scarce research that explores the association of personal networks of community members in their LPG adoption. In this cross-sectional study, we use standard egocentric personal network analyses and multivariate logistic regression models to examine the association of structure and composition of personal networks with LPG adoption in poor communities. Our results show that higher proportions of peers owning LPG are associated with higher likelihood of LPG ownership in the respondents (OR = 41.30, 95% confidence interval: 16.86–101.20, p = 0.00). This study on personal network characteristics in clean cooking research offers a germane foundation for further large scale personal network studies on clean cooking adoption in poor communities.